Management maintenance system for remote control based on microcontroller and virtual private server - Idham Kamil; Julham Julham; Muharman Lubis; Arif Ridho Lubis (Institute of Advanced Engineering and Science, 2019)
Open loop shaped control system is a form of system control without any feedback from the system. One example is the on-off condition which functions to connect and disconnect electricity. The condition to be studied is a dc motor that can be set to live and die via internet server-based client service. The server in this system is a virtual private server (VPS) device that will provide a source of service to the client in the form of a collection of information on dc motor conditions. In addition, its function is also to record the working time of the dc motor. So that a schedule can be determined when the dc motor is maintained. While the client is a control unit consisting of a microcontroller device, an ethernet module enc28j60 and a dc motor. In general the working principle of the system is beginning with the user accessing the desired VPS IP address through a web browser application. From the web browser the user chooses a dc motor to be activated. But before the client has been connected to the VPS regularly (every second), the point is to always get the latest dc motor condition information. Then the microcontroller will set the dc motor in active or off condition. The research method used is research and development. The results obtained from this study are that the amount of bandwidth needed for communication between VPS and microcontrollers via the internet network, when the control unit works is 6.02 kbps, while the response time for dc motor is 3.16 seconds and the response time for dc motor 2 is 3.46 seconds.